IMPLEMENTASI WEB SERVICE DALAM PENGEMBANGAN SISTEM INFORMASI DESA BERBASIS ANDROID PADA DESA DARMASARI KECAMATAN SIKUR KABUPATEN LOMBOK TIMUR - fathurrahman, imam; Saiful, Muhammad (Fakultas Teknik Universitas Hamzanwadi, 2019)
The Village Office of Darmasari, Sub-district of Sikur is a fairly new office of the village. Darmasari Village is a part of the Semaya Village Expansion which was inaugurated on November 15, 2010. When the present researcher got the opportunity to observe it, the researcher took the initiative to develop an existing system which is called SID, became an android-based system which would help in the dissemination and get information quickly. After carrying out the analysis and conducting several interviews with the village staff, the Darmasari Village Office indeed needed an Android Application as a liaison medium between village officials and the community which would certainly be more efficient than its use and from the previous method of having to access the website in the browser. In realizing the development of this SID system, the present researcher used the SID Web server as the main ingredient, XAMPP as a server, and Android Studio as the media for making Android applications. This Android-based SID Darmasari can be used to help and make it easier for people to receive information quickly in public services to be more efficient.DOI : 10.29408/jit.v2i2.1459